CDMA - Dong Geun Jeong (IEEE Journal on selected areas in communications)
This paper proposes a code division multiple access (CDMA) time division duplex (TDD) system for wireless multimedia services with traffic unbalance between uplink and downlink. In the proposed system, the number of uplink time slots in a TDD frame differs from that of downlink. Moreover, the difference can be reset by the network operator according to the traffic pattern. We evaluate the performance of the proposed system under multimedia environment using Markov analysis and computer simulation. The results show that the frequency utilization is maximized even when the uplink and downlink traffic volumes are unbalanced. This, in turn, reduces drastically the blocking rate of multimedia calls (connections) in the proposed system compared with that in the traditional CDMA systems where the uplink and downlink use equal bandwidth